Efektivitas Pembelajaran Tradisional Vs Smart Technology dalam Meningkatkan Kemampuan Membaca Al-Quran di Sekolah Al-Anshar Tanjung Selor - Rahmawati, Rahmawati; Nurfitriana, Nurfitriana; Haditia, Mohamad (Lembaga Sosial Rumah Indonesia, 2023)
The purpose of this study is to address learning disparities by conducting an in-depth analysis of the effectiveness of conventional learning and smart-technology–based learning supported by smart pedagogy in Qur’an learning activities. In the era of smart technology, the integration of technological tools has become increasingly relevant; however, empirical evidence comparing Qur’an learning outcomes between technology-based methods and traditional approaches remains limited. Traditional methods still offer notable advantages, particularly in environments with limited access to technology. This study employed a quasi-experimental design using a pre-test–post-test control group model and involved 30 students selected through total sampling. The participants were randomly assigned to two groups (conventional and smart technology). Data analysis was carried out using a one-way ANOVA after meeting the assumptions of normality (Shapiro–Wilk test) and homogeneity of variance (Levene’s test). The Shapiro–Wilk normality test for the conventional and smart-technology groups yielded values of 0.099 and 0.069, respectively. Since both values exceed 0.05, the data were considered normally distributed. The homogeneity test using Levene’s Test (Based on Mean) resulted in a value of 0.733, which is also greater than 0.05, indicating that the variances of both groups were homogeneous. Furthermore, the ANOVA analysis produced a significance value of 0.0359. Because this value is below 0.05, it can be concluded that there is a significant difference in effectiveness between the conventional learning method and the smart-technology method. The results demonstrate that digital learning supported by smart pedagogy and smart technology is significantly more effective in improving students’ Qur’an reading abilities than traditional methods. These findings support the need for curriculum reform to integrate advanced technologies and adaptive learning strategies into Qur’an education.